Anti‐inflammatory activities and glycerophospholipids metabolism in KLA‐stimulated RAW 264.7 macrophage cells by diarylheptanoids from the rhizomes of Alpinia officinarum. (2nd October 2017) - Zhang, Guogai; Zhao, Lifang; Zhu, Jiancheng; Feng, Yifan; Wu, Xia
Abstract: Alpinia officinarum is used for its anti‐inflammatory activity historically in China. Diarylheptanoids isolated from A. officinarum play important biological roles in the prevention and treatment of inflammatory disorders. Seven diarylheptanoids (1–7) were isolated from A. officinarum . The cell viabilities and anti‐inflammatory activities of diarylheptanoids were evaluated by MTT assay and tumor necrosis factor‐ α production in Kdo2‐lipid A‐stimulated RAW 264.7 cells in vitro . The relationships between their anti‐inflammatories and structure‐activities are discussed. The results indicated that compounds 1 and 3–7 had significant anti‐inflammatory activities. The relationships between inflammation and phospholipids metabolism were elucidated by multivariate data analysis. Twenty‐two potential biomarkers were identified in inflammatory group vs. blank group, and 11 potential biomarkers were identified for inflammatory group vs. drug‐treatment groups. Ten common phospholipids were characterized. On the basis of a previous study in our laboratory, we found that phosphatidylethanolamine (18:0/18:1) might be the important glycerophospholipid biomarker in inflammation. In this study, we firstly combined anti‐inflammatory activities and glycerophospholipids changes of traditional Chinese medicine. This work suggests that the anti‐inflammatory activities of diarylheptanoids might be significantly related to glycerophospholipids and could provide a useful database for investigating the anti‐inflammatory effects of traditional Chinese medicine.